Inside Back Cover: Synthesis of Carbon‐Supported Pt–YOx and PtY Nanoparticles with High Catalytic Activity for the Oxygen Reduction Reaction Using a Microwave‐based Polyol Method (ChemCatChem 6/2017). Issue 6 (20th March 2017) - Tsuji, Masaharu; Uto, Keiko; Nagami, Tetsuo; Muto, Akiko; Fukushima, Hideoki; Hayashi, Jun‐ichiro
Abstract : The Cover shows carbon‐supported PtY alloy nanoparticles with a high catalytic activity for the oxygen reduction reaction, which are promising catalysts for use in proton exchange membrane fuel cells.In their Full Paper, M. Tsuji et al. demonstrate a novel synthesis of Pt–YO x /C and PtY/C alloy catalysts under microwave heating followed by acid treatment. Their high catalytic activity might be attributed to surface structural changes of Pt nanoparticles generated by the presence of YO x and Y atoms leading to modification of the adsorption energy of OH at the Pt sites.